2010
DOI: 10.5551/jat.2600
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Role of Markers of Inflammation in Atherosclerosis

Abstract: In recent years, several studies have used the measurement of carotid intima-media thickness (IMT) as a marker of early atherosclerosis: IMT has been shown to correlate significantly with the presence of coronary artery disease (CAD) and to predict fatal and not fatal cerebro-and cardio-vascular events. These findings highlight the importance of recognizing and managing early stages of atherosclerosis for effective cardiovascular prevention. Beyond traditional established cardiovascular risk factors, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 48 publications
7
103
2
4
Order By: Relevance
“…Recent observations have suggested that inflammation may also be a possible link between coronary and carotid instability. 21) In our study, instead, the degree of inflammation observed at histology was No inflammation (-) was present in 54% of patients in group A, and in 28% of patients in group B, (P = 0.031). There was no significant difference for subclass "+", while subclass "++" resulted at the limits of statistical significance, a marked inflammatory infiltration being present only in 9% of group A patients, versus 30% of group B patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recent observations have suggested that inflammation may also be a possible link between coronary and carotid instability. 21) In our study, instead, the degree of inflammation observed at histology was No inflammation (-) was present in 54% of patients in group A, and in 28% of patients in group B, (P = 0.031). There was no significant difference for subclass "+", while subclass "++" resulted at the limits of statistical significance, a marked inflammatory infiltration being present only in 9% of group A patients, versus 30% of group B patients.…”
Section: Discussionmentioning
confidence: 54%
“…6,15,16) Moreover, the amount of calcium and the rapid progression of calcification at the coronary arteries level have been associated in previous works with a higher risk of cardiovascular events. [17][18][19][20][21] Therefore, carotid calcifications could reflect diffuse coronary artery disease. Our study demonstrates that the presence of an extensively calcified carotid plaque is strongly suggestive of the likelihood of an acute coronary event or at least a warning sign of advanced coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…of visceral adiposity in some studies (33,34) and is known to be closely linked to carotid intima-media thickness (35). In addition, nonalcoholic steatohepatitis can predict a more atherogenic risk profile (34).…”
Section: Relationship Of Circulating Ccdc80 Protein To Obesity In Humansmentioning
confidence: 99%
“…Two such markers are the inflammatory protein high-sensitive C-reactive protein (hs-CRP), which is related to cardiovascular disease and is stimulated by the proinflammatory cytokine interleukin 6 (IL6) (10), and the N-terminal pro-brain natriuretic peptide (NT-proBNP), used as a diagnostic parameter for congestive heart failure (11). Previous studies on patients with active acromegaly have shown lower than normal values of hs-CRP in most (9,12,13,14,15), but not all studies (16).…”
Section: Introductionmentioning
confidence: 99%